EFFECT OF DIETARY RED YEAST (Sporidioboluspararoseus) SUPPLEMENTATION ON SMALL INTESTINAL HISTOMORPHOMETRY OF LAYING HENS - W. Tapingkae; P. Yindee; T. Moonmanee (Journal of Animal and Plant Sciences, 2016)
This study aimed to evaluate the effect of dietary supplementation with red yeast (Sporidiobolus paraeoseus) on small intestinal morphology and determine the correlation of red yeast supplementation on intestinal morphology in laying hens. One hundred sixty laying hens were randomly assigned into four dietary groups as follows: basal diet (control) and basal diet with red yeast supplementation at 0.5 (R1), 1.0(R2), and 2.0(R3) g/kg feed. After 12 weeks of feeding, 16 hens (4from each group) were randomly euthanized and the small intestines collected to determines mall intestinal morphology. The villus height of the duodenum was higher in R1, R2, and R3 red yeast-supplemented groups compared to the control-treated group. However, dietary treatments did not differ significantly in terms of jejunal and ilealmorphology data (villus height and width, crypt depth, villus height/crypt depth ratio, crypt area, and muscularis mucosae thickness). A positive linear correlation was also observed between the level of red yeast supplementation and the width of jejunal villi (R2=0.8992).In conclusion, red yeast supplementation in the diet improved duodenal lumen health of laying hens by enhancing duodenal villus height.
Keywords: red yeast; laying hen; small intestinal morphology; prebiotic